2023
DOI: 10.18280/ijsdp.180132
|View full text |Cite
|
Sign up to set email alerts
|

Determinants on Small Scale Business: An Empirical Evidence from Indonesia

Abstract: In 1997-1998, the resilience of small and medium enterprises (SMEs) was tested when the monetary recession paralysed Indonesia. At that time, only SMEs were detected as shining and the most prominent from other sectors. This study is oriented to investigate the effect of the quality of human resources (HR), capital, and business length on turnover, labor cost, market share, and profit. The study design is offline survey, where primary data is collected from a sample that invites 285 respondents in three zones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…The connection between digital administration skills and profits is revealed in several manuscripts (Ciruela-Lorenzo et al, 2020;Feyen et al, 2021;Hasbullah and Bareduan, 2021;Jorge-Vázquez et al, 2021;Wijaya et al, 2023;Xie et al, 2016) implications for public policy. Technology providers enhance the asymmetric exchange of information and enable economic forces to bring major advances to the global market structure.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between digital administration skills and profits is revealed in several manuscripts (Ciruela-Lorenzo et al, 2020;Feyen et al, 2021;Hasbullah and Bareduan, 2021;Jorge-Vázquez et al, 2021;Wijaya et al, 2023;Xie et al, 2016) implications for public policy. Technology providers enhance the asymmetric exchange of information and enable economic forces to bring major advances to the global market structure.…”
Section: Discussionmentioning
confidence: 99%
“…This study has the following contributions. First, limited researches have focused on social media usage in the SME context (Darma, 2020;Istikhoroh et al, 2021;Wijaya et al, 2023) , and the current research aims to fill this gap. Second, there is an enlarging focus on the casual system underlying the association between social media adoption (Tabassam, 2023) and SME job performance (Qureshi et al, 2023); however, studies indicated that the empirical evidence of social media from a theoretical perspective is still insufficient.…”
Section: Research Gapmentioning
confidence: 99%
“…Social and political capital is an important variable for the growth and development of cooperatives and MSME Associations, the impact of small-scale traditionally managed business units so that interaction between MSME becomes more massive MSME has a classic and fundamental problem until now, namely competitiveness [5]. This competitiveness is related to the productivity that arises from innovations that arise from the ability of the workforce, the development of cooperatives and MSME Associations will have an impact on improving people's welfare which has a broad impact on improving the national economy [6].…”
Section: Introductionmentioning
confidence: 99%